Analisis Komponen Fisik Terhadap Kemampuan Passing Cabang Olahraga Futsal Siswa SMA Negeri 8 Makassar - Achmad Karim; Muhammad Akbar Syafruddin; Ikadarny Ikadarny; Muhammad Hasbillah (Gerak: Journal of Physical Education, Sports, and Health, 2023)
This study aims to determine the relationship between leg muscle strength on passing ability, the relationship between balance and passing ability, and the relationship between leg muscle strength and balance on the passing ability in futsal sports for students of SMA Negeri 8 Makassar Makassar. This type of research is correlational with Quantitative Research Methods. The research population was SMA Negeri 8 Makassar students and 30 samples were taken. The technique of determining the sample is random (random sampling) by drawing lots. The analysis technique used was descriptive analysis, correlation analysis, regression analysis and the data were analyzed using the SPSS version 21 application. The results showed that 1). There is a significant relationship between leg muscle strength and passing ability in futsal sports with a correlation value (R) = 0.800. 2). There is a significant relationship between balance and passing ability in futsal sports with a correlation value (R) = 0.594. 3). There is a significant relationship between leg muscle strength and balance on the passing ability of futsal sports with a correlation value (R) = 0.800, and with a coefficient of determination (r2) = 0.641 or equal to 64.10%. Thus it can be concluded that there is a significant relationship between leg muscle strength and balance on the passing ability of futsal sports